India - Singh, Sarina; Blasi, Abigail; Benanav, Michael; Clammer, Paul; Elliot, Mark; Harding, Paul; Holden, Trent; Mahapatra, Anirban; McCrohan, Daniel; Noble, John; Noble, Isabella; Raub, Kevin; et al. (Lonely Planet guidebooks., 2015)
"India is a complex beauty: temples, frenetic bazaars, crumbling fortresses, jungles, Himalayan mountains and the jostle of city life to embrace India s unpredictability is to embrace her soul. Sarina Singh, Lonely Planet Writer "Getting you to the heart of a place"Amazing experiences Inspirational images, 3D illustrations, city walks and the best of local knowledge. Plan the perfect trip Planning features and top itineraries give you the freedom to create your ideal trip. Find hidden travel gems. Our authors uncover local secrets that will make your trip unique. Special Features Taj Mahal in 3D. Detailed plans for top sights Women Travelers advice. Illustrated temple feature We tell it like it is Our job is to make amazing travel experiences happen. We visit the places we write about each and every edition. We never take freebies for positive coverage, so you can always rely on us to tell it like it is."